2020
DOI: 10.1186/s12864-020-07198-2
|View full text |Cite
|
Sign up to set email alerts
|

GWAS unveils features between early- and late-flowering pearl millets

Abstract: Background Pearl millet, a nutritious food for around 100 million people in Africa and India, displays extensive genetic diversity and a high degree of admixture with wild relatives. Two major morphotypes can be distinguished in Senegal: early-flowering Souna and late-flowering Sanio. Phenotypic variabilities related to flowering time play an important role in the adaptation of pearl millet to climate variability. A better understanding of the genetic makeup of these variabilities would make it… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 27 publications
2
12
0
Order By: Relevance
“…High allelic variation and polymorphism were recorded between pairs of parental lines of pearl millet after screening with SNP markers, and they were also mapped on all the seven linkage groups reflecting the distribution of the markers in the genome (Sehgal et al, 2012). Similarly, a panel 21,663 SNP markers were also discovered, depicting > 5% of minor allele frequencies by Diack et al (2020). Different types of molecular markers and genomic approaches ultimately provide a systematic knowledge on plant biology enabling MAB, which can accelerate the process of the development of new and resistant hybrids/varieties.…”
Section: Climate Resilience In Pearl Millet and Genomic Resourcesmentioning
confidence: 97%
“…High allelic variation and polymorphism were recorded between pairs of parental lines of pearl millet after screening with SNP markers, and they were also mapped on all the seven linkage groups reflecting the distribution of the markers in the genome (Sehgal et al, 2012). Similarly, a panel 21,663 SNP markers were also discovered, depicting > 5% of minor allele frequencies by Diack et al (2020). Different types of molecular markers and genomic approaches ultimately provide a systematic knowledge on plant biology enabling MAB, which can accelerate the process of the development of new and resistant hybrids/varieties.…”
Section: Climate Resilience In Pearl Millet and Genomic Resourcesmentioning
confidence: 97%
“…Allelic diversity of PgPHYC and PgMADS11 genes were assessed in landraces of pearl millet and the results revealed that the early flowering landraces carried allele for early flowering at PgPHYC locus and PgMADS11 locus showed significant differences in genotype frequencies (Diack et al 2017 ). In another study, Diack et al ( 2020 ) identified one SNP that is located on PgPPR gene encodes a pentatricopeptide repeat protein belonging to ATP DNA-binding cassette family involved in plant resistance and defense. Additionally, they identified one SNP on PgAAO1 gene that encodes an indole-3-acetaldehyde oxidase.…”
Section: Genetic Analysis Of Important Adaptive and Agronomic Traits ...mentioning
confidence: 99%
“…Association mapping in pearl millet revealed that there was a significant marker traits association for various agronomic traits such as stover dry matter yield, fresh stover yield, panicle harvest index, spike length, and so on (Varshney et al 2017 ). For tillering, one SNP on PgHK4 gene was identified which encodes a histidine kinase but no SNPs were identified for biomass (Diack et al 2020 ).…”
Section: Genetic Analysis Of Important Adaptive and Agronomic Traits ...mentioning
confidence: 99%
“…Landrace variability has already been exploited by farmers to shorten flowering cycles, as a response to the 1970s and 1980s drought episodes, while conserving their varieties ( Vigouroux et al, 2011 ; Dussert et al, 2015 ). Substantial effort has been made in the past decades to investigate genes associated with flowering cycle in pearl millet ( Saïdou et al, 2009 ; Vigouroux et al, 2011 ; Lakis et al, 2012 ; Kumar et al, 2017 ; Diack et al, 2020 ). To date, only the role of PgPHYC gene has been really validated and some other QTLs were identified ( Saïdou et al, 2009 ; Kumar et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…We previously used the core collection from Senegal to identify genes involved in the agromorphological differentiation of the two flowering groups ( Diack et al, 2020 ). This study identified a number of genetic markers associated with biomass, but did not identify genes clearly involved in flowering.…”
Section: Introductionmentioning
confidence: 99%